IMPLIKASI RESES ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN INDRAGIRI HILIR DALAM PERSPEKTIF DEMOKRASI PERWAKILAN (STUDI DAERAH PEMILIHAN VI (ENAM)) - Ayunika Ayunika; Dessy Artina; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Law Number 23 of 2014 concerning Regional Government is contained in Article 108 Letter I, Article 161 Letter I, which reads "what is meant by "recurring work visits" is the obligation of members of the Regency/Municipal DPRD to meet with their constituents regularly at every period. recess, the results of which meetings with constituents are reported in writing to political parties through their factions in the Regency/Municipal DPRD”. That DPRD members among others have the obligation to absorb, collect constituents' aspirations through regular working visits, accommodate and follow up on community aspirations and complaints. DPRD members and their representatives have their respective electoral districts or abbreviated as DAPIL. One example is in the constituency VI (six) of the downstream Indragiri Regency, there are 4 subdistricts that are members of the DAPIL, namely Keritang District, Reteh District, Sungai Batang District, and Kemuning District. Here the author specializes in Keritang District and Reteh District. Where the area is not translated by peopleso that there is omission in the area. Within the DAPIL there are several council members who have their respective sub-districts who are members of the DAPIL VI (six).This study uses a sociological legal research type. This research is descriptive in nature, namely research that seeks to systematically and carefully provide facts with certain population characteristics. The results of the research conducted by the authors of the implementation of the recess, especially in Keritang District, and Reteh District, Electoral District VI, Indragiri Hilir Regency have not been implemented or have not had good implications, where council members conduct recess only for formalities, recess implementation is also carried out in certain areas. Council members conduct a recess in the regions that win the most votes at the time of the general election. Therefore, the author offers the existence of rules in the Government Regulation of the Republic of Indonesia Number 12 of 2018 concerning Guidelines for the Preparation of Orders for the Provincial, Regency, and City Regional House of Representatives regarding the obligation for members of the House of Representatives. the council conducts recess throughout the villages that are its constituencies.Keywords: Recess, DPRD, Recess Implementation.